Myxovirus resistance, osteopontin and suppressor of cytokine signaling 3 polymorphisms predict hepatitis C virus therapy response in an admixed patient population: comparison with IL28B (Clinics, 2013)
OBJECTIVES: Suppressor of cytokine signaling 3, myxovirus resistance protein and osteopontin gene polymorphisms may influence the therapeutic response in patients with chronic hepatitis C, and an association with IL28 might increase the power to predict sustained virologic response. Our aims were to evaluate the association between myxovirus resistance protein, osteopontin and suppressor of cytokine signaling 3 gene polymorphisms in combination with IL28B and to assess the therapy response in hepatitis C patients treated with pegylated-interferon plus ribavirin. METHOD: Myxovirus resistance protein, osteopontin, suppressor of cytokine signaling 3 and IL28B polymorphisms were analyzed by PCR-restriction fragment length polymorphism, direct sequencing and real-time PCR. Ancestry was determined using genetic markers. RESULTS: We analyzed 181 individuals, including 52 who were sustained virologic responders. The protective genotype frequencies among the sustained virologic response group were as follows: the G/G suppressor of cytokine signaling 3 (rs4969170) (62.2%); T/T osteopontin (rs2853744) (60%); T/T osteopontin (rs11730582) (64.3%); and the G/T myxovirus resistance protein (rs2071430) genotype (54%). The patients who had ≥3 of the protective genotypes from the myxovirus resistance protein, the suppressor of cytokine signaling 3 and osteopontin had a greater than 90% probability of achieving a sustained response (p